تأثير تطبيق اللعبة “SCATTERGORIES“ نحو ترقية مهارة الكتابة - Sholehan; Fauzi, Ahmad; Subahah, Nurus; Santhi, Peta Fristy; Murteza, M. Ali (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
One of the language games that are considered interesting in learning Arabic is Scattergories. This game is a way of learning that requires students to learn a lot of vocabulary and write a lot. In addition, students will be more enthusiastic, also improve writing skills and remember new vocabulary. The purpose of this study is to reveal whether or not there is an effect of the application of the scattergories game method in improving students’ writing skills. Learning to practice writing skills using the "scattergories" game method was well received by students. But on the other hand, before learning begins, you should first introduce vocabulary related to the material, so that students do not ask questions continuously when students have started the game. The results showed that the application of the game "scattergories" had an effect on improving students’ writing skills.